Role of the Preoptic Area in Sleep and Thermoregulation - Rothhaas, Rebecca; Chung, Shinjae (Frontiers in Neuroscience, 2021)
Sleep and body temperature are tightly interconnected in mammals: Warming up our body helps to fall asleep and the body temperature in turn drops while falling asleep. The preoptic area of the hypothalamus (POA) serves as an essential brain region to coordinate sleep and body temperature. Understanding how these two behaviors are controlled within the POA requires the molecular identification of the involved circuits and mapping their local and brain-wide connectivity. Here, we review our current understanding of how sleep and body temperature are regulated with a focus on recently discovered sleep- and thermoregulatory POA neurons. We further discuss unresolved key questions including the anatomical and functional overlap of sleep- and thermoregulatory neurons, their pathways and the role of various signaling molecules. We suggest that analysis of genetically defined circuits will provide novel insights into the mechanisms underlying the coordinated regulation of sleep and body temperature in health and disease.